Penerapan Instrumen Non Tes serta Kesulitan yang Dihadapi di SD Negeri Balaraja III Kabupaten Tangerang - Magdalena, Ina; Oktania, Alifah; Destiana, Della; Sipayung, Kristin Novita Sari; Sari, Putri Indah; Putri, Rizka Surya (YASIN, 2022)
This study aims to try to apply non-test instruments to students and analyze the learning process using non-test instrument methods at SD NEGERI BALARAJA III Kab. Tangerang. In this study using a qualitative approach and the method used in this study is the method of description. This method focuses attention on the problem directly how it was at the time the research took place, in this case the researcher tried to describe the events and incidents that were the center of attention in the study without giving special treatment to them at SD NEGERI BALARAJA III Kab. Tangerang. The data collection technique in this study was carried out by direct interviews with one of the teachers who taught class IV named Yanti Puspita Sari, S.Pd at SD NEGERI BALARAJA III Kab. Tangerang as a guest speaker. The research results obtained indicate that on average the teachers in this school have started using non-test instrument assessments in carrying out assessment activities on students. Although some teachers find it difficult to apply non-test instruments at SD NEGERI BALARAJA III Kab. Tangerang and the school will always evaluate teachers and find solutions to problems encountered in this non-test instrument method.